Drivers of procurement performance in the public health industry in the Gauteng province - Masemola, Shilela Catherine (Vaal University of Technology, 2022)
The purpose of this study was to investigate the relationship between supplier selection practices, supplier risk management, supplier commitment and procurement performance in the public health industry in Gauteng province. Many studies have been conducted on the specific subject of procurement performance within the public health care sector. However, there is very little evidence that any such studies have been carried out that have precisely been narrowed down to the specific subject of the dimensional relationships and linkages between Supplier selection, supplier risk management, supplier commitment and procurement performance in the public health industry in South Africa. This study, therefore, was conducted to fill this gap. To measure the study constructs, the survey material was designed in the form of a structured questionnaire. Participants were asked to complete four test instruments namely: supplier selection questionnaire, supplier risk management questionnaire, supplier commitment and procurement performance questionnaire. A total number of 200 questionnaires was distributed to the identified sample of public health industries of which 187 responded and finally, 150 questionnaires were usable and used for data analysis. The collected quantitative data were analysed using the SMART-partial least squares (SMART-PLS 3) structural equation modelling procedure. The actual data analysis techniques applied included descriptive statistics and inferential statistics using structural equation modelling. Also, the latter used a SMART-PLS 3 to test the psychometric properties of measurement scales and the testing of the six hypotheses using the path analyses technique. The results of the study showed positive and significant relationships amongst all variables except for one. Specifically, supplier selection and supplier risk management exerted a moderate and significant influence on supplier commitment. Moreover, supplier commitment had a strong positive and significant relationship with procurement performance while supplier risk management had a weak and insignificant relationship with the same factor. More results provided from the analysis confirmed the existence of a very strong and significant relationship between supplier selection and procurement performance. Besides, the study takes note of its contributions to highlighting its merits. From a theoretical perspective, it provides an in-depth examination of some driving factors to supplier selection, supplier risk management, supplier commitment and procurement performance within Public health entities. Given that a study of this nature has not been performed before amongst South African public health care sectors, the results are an essential addition to the existing body of literature within the area of procurement performance within public health industries in developing countries such as South Africa. The study concludes by suggesting recommendations for limiting the impact of the identified challenges on procurement performance.
M. Tech. (Department of Logistics, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supplier selection; Supplier commitment; Supplier risk management; Procurement; Dissertations, Academic -- South Africa.; Business logistics -- Gauteng (South Africa).